Clitorea ternatea flower extract induces platelet-derived growth factor (PDGF) and GPx gene overexpression in ultraviolet (UV) B irradiationinduced collagen loss - Rizka Sofyanti Putri; Agung Putra; Dr Chodidjah; Dewi Masyitah Darlan; Setyo Trisnadi; Siti Thomas; Nur Dina Amalina; Rizky Candra Irawan (Medicinski glasnik, 2022)
Aim: To determine the effect of Clitorea ternatea flower extract (CTFE) in the gel dosage form on the expression of GPx and platelet-derived growth factor (PDGF) in ultraviolet (UV) - B irradiation-induced collagen loss rat model. Methods: This is experimental research with post-test control group design. Twenty healthy male Wistar rats were divided into four treatment groups: a sham group, UVB control group, two treatment groups with gel of CTFE 5% and gel of CTFE 10%, respectively. Each group was treated with UVB at 302 nm with a MED of 160 mJ/cm2 for 5 days, whereas the sham group did not receive UVB. In the treatment groups CTFE 5% and CTFE 10% gel were given on the 6th to the 14th day. On day 14 all treatment groups were terminated, and GPx and PDGF gene expression were analysed using qRT-PCR. Results: In the group of gel of CTFE 10%, there was a significant increase in GPx gene expression (9.51±1.83) and PDGF (4.36±1.18) compared to the UVB control group which had GPx and PDGF gene expression of 4.90±1.64) and 0.032±0.01, respectively. Conclusion: The administration of CTFE gel showed an increase of the expression of GPx and PDGF genes on UVB irradiationinduced collagen loss rat model.
Keywords: clitorea ternatea flower extract; collagen loss; GPx; PDGF